CHARACTERISTICS OF AGAVE SISALANA NATURAL FIBER COMPOSITES WITH SEAWATER TREATMENT - Raviko, Johansyah; Purnowidodo, Anindito; Wahyudi, Slamet; Azmi, Muhammad (International Journal of Mechanical Engineering Technologies and Applications, 2025)
This study focuses on the more environmentally friendly treatment (seawater treatment) than classical chemical treatments (natural fibers and a new trend of developing epoxy resin matrix composites with natural Agave Sisalana fiber reinforcement). The current study investigated natural agave sisalana fiber soaked in seawater for three days and seven days to increase the adhesion of the fiber-matrix interface on the epoxy resin composite with natural agave sisalana fiber. The best single fiber tensile strength test was caught on the 7-day treatment sample, where the loss was 898.49 MPa, and the modulus of elasticity was 1418.42 MPa. From the results of the SF composite tensile strength test, the highest tensile strength value was obtained in the 7-day seawater treatment sample of 103,734 MPa, the elongation at break value was 23,954 MPa, and the modulus of elasticity was 4,576 MPa. The data revealed that samples with the given treatment had higher mechanical properties than those without treatment. The loss of impurities in the sisal fiber after seawater treatment leads to a better bond between the fibers and the matrix, where the high value of tensile strength was influenced by the interface bond between the sisal fiber and the strong epoxy resin matrix acting as a load support. Furthermore, the macro photo data reveals that the results of the tensile testing fracture experienced a ductile fracture because it was marked that the fiber pull-out mechanism dominated in each specimen, piloting the reinforced sisal fiber composites experience slow cracking. In conclusion, seawater treatment may strengthen the fibers' mechanical surface properties by removing the outer layers of hemicellulose, cellulose, and lignin, causing the fiber-matrix interface to increase, leading to higher direct impact and tensile strength than composites with no seawater treatment.